RANCANG BANGUN MESIN PENCACAH LIMBAH KELAPA - Rizki Ramdani; Agus Saleh; Adittya Prajas (UPPM Politeknik TEDC Bandung, 2022)
Coconut fiber and shells are often considered as waste and thrown away. Several studies say that in fact, coconut waste can be processed into useful products. Coconut waste can be used as material for biobriquettes, handicrafts, planting media and mixtures for building materials. Of course, the use of coconut waste to become a useful product, must go through a processing process first. To help the process, it can be done with the application of technology. The technology in question is in the form of a coconut waste chopping machine. It aims to make the processing more effective in terms of time and safer. Based on these reasons, the author is interested in making a coconut waste chopper machine. Broadly speaking, the stages in the manufacture of coconut waste chopping machines start from the design stage, the manufacture & assembly stage and the testing stage. Based on the test results, it is known that the power generated by the coconut waste chopper machine is 5.5 HP at 3600 rpm rotation. The capacity obtained from the coconut waste chopping machine is 20.4 Kg/hour.